A novel bioaccessibility-based probabilistic risks assessment of potentially toxic elements (PTEs) in earthworm - Zuo, Tian-Tian; Liu, Jia-Lin; Jin, Hong-Yu; Chang, Yan; Wei, Feng; Wei, Sheng; Kang, Shuai; Ma, Shuang-Cheng (Frontiers in Pharmacology, 2024)
Early risk assessment studies usually based on total heavy metal(loid) contents, inevitably leading to an overestimation of the health risks. In addition, inputs are represented as single-point estimates in deterministic models, leading to underestimation or overestimation of the health risks. To overcome these barriers, a novel probabilistic risk assessment strategy based on the combinational use of bioaccessibility and Monte Carlo simulation was developed to assess heavy metal(loid) associated health risks of earthworms in this study. To obtain a realistic and robust probabilistic risk assessment, heavy metal(loid) exposure duration and frequency were determined using our questionnaire data. As a result, the mean gastrointestinal bioaccessibility was in the order: Cd>As>Cu>Hg. The mean hazard index (HI) values for investigated metal(loid)s were 0.65 and 0.59 for male and female, respectively, demonstrating an acceptable health risk in an average community. However, the 90th percentile of HI values was 1.87 and 1.65 for male and female, respectively. And the total non-cancer risks of heavy metal(loid) exposure exceeded the acceptable threshold for 19.9% and 17.8% of male and female, respectively. In addition, the total cancer risk (TCR) value through co-exposure to As and Cd suggested that the carcinogenic risks may be of concern for average exposure population. Sensitivity analyses revealed that the exposure frequency and bioaccessible As concentration were the dominant contributors to the total risk variance, which provided meaningful implications for environmental management. Altogether, the refined strategy based on bioaccessibility 4 and Monte Carlo simulation is the first of its kind, such effort attempts to scientifically guide the rational clinic use of TCM and the improvement of population-health.